Technical resource paper, regional workshop on the culture and utilization of seaweeds vol. II. (Regional Seafarming Development and Demonstration Project, Network of Aquaculture Centres in Asia, 1990)
Regional Seafarming Development and Demonstration Project RAS/90/002